2020
DOI: 10.1093/jxb/eraa050
|View full text |Cite
|
Sign up to set email alerts
|

Gynoecium size and ovule number are interconnected traits that impact seed yield

Abstract: Angiosperms form the largest group of land plants and display an astonishing diversity of floral structures. The development of flowers greatly contributed to the evolutionary success of the angiosperms as they guarantee efficient reproduction with the help of either biotic or abiotic vectors. The female reproductive part of the flower is the gynoecium (also called pistil). Ovules arise from meristematic tissue within the gynoecium. Upon fertilization, these ovules develop into seeds while the gynoecium turns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 101 publications
2
57
0
Order By: Relevance
“…The third batch of ovule primordia initiated normally at the bottom and top of the placenta and significantly differ from the size and shape of the first two groups. Our hypothesis illustrated the ovules population initiation is an interrelated process.Up until now, published models mainly described single ovule primordium initiation Development • Accepted manuscript and the signals among the primordium and its two boundaries (Galbiati et al 2013;Cucinotta et al, 2020). Our hypothesis described the relationship of neighboring ovule primordia during the initiation.…”
Section: Asynchronous Ovule Primordia Initiation Is Important For Plamentioning
confidence: 89%
See 1 more Smart Citation
“…The third batch of ovule primordia initiated normally at the bottom and top of the placenta and significantly differ from the size and shape of the first two groups. Our hypothesis illustrated the ovules population initiation is an interrelated process.Up until now, published models mainly described single ovule primordium initiation Development • Accepted manuscript and the signals among the primordium and its two boundaries (Galbiati et al 2013;Cucinotta et al, 2020). Our hypothesis described the relationship of neighboring ovule primordia during the initiation.…”
Section: Asynchronous Ovule Primordia Initiation Is Important For Plamentioning
confidence: 89%
“…These genes include those encoding multiple MADS-box transcription factors and other regulators, such as AGAMOUS (AG), SEEDSTICK (STK), SHATTERPROOF1 (SHP1), SHP2 and SEPALLATA (SEP) ( Bowman et al, 1989 ; Honma and Goto, 1996 ; Theißen et al, 1996 ; Favaro et al, 2003 ), and AINTEGUMENTA (ANT), BELL1 (BEL1), APETALA2 (AP2) and HUELLENLOS (HLL) ( Modrusan et al, 1994 ; Reiser et al, 1995 ; Elliott et al, 1996 ; Schneitz et al, 1998 ; Brambilla et al, 2007 ). Multiple hormones are also involved in ovule development and regulate ovule number through influencing gynoecium development, carpel fusion and CMM formation, processes that affect placenta development and ovule identity ( Colombo et al, 2008 ; Reyes-Olalde et al, 2013 ; Marsch-Martínez and de Folter, 2016 ; Zúñiga-Mayo et al, 2019 ), including auxin, brassinosteroid (BR), cytokinin (CK) and gibberellin (GA) ( Cucinotta et al, 2020 ). The weak mutant of the auxin efflux facilitator PIN-FORMED1 (PIN1), pin1-5 , displays a reduction in ovule number ( Bencivenga et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, increased levels of CKs in ckx3ckx5 double mutant lead to an increase in gynoecium size and to the formation of more ovules, due to increased meristematic activity of the placenta tissue [20,21]. Moreover, it has been also reported for other Brassicaceae species that CKs influence ovule number, suggesting that the genetic manipulation of CK metabolism is a potentially powerful tool to enhance seed yield [19,22]. Intriguingly, however, it was recently demonstrated that high levels of CKs in ckx7 mutants inhibited fruit elongation [23].…”
Section: Cytokinins Play a Pivotal Role In Ovule Patterning And Develmentioning
confidence: 98%
“…During this process, the two inner and outer integuments surrounding the developing female germline develop and after three rounds of mitosis, the FM gives rise to the FG in a process called megagametogenesis (Figure 2a). Moreover, it has been also reported for other Brassicaceae species that CKs influence ovule number, suggesting that the genetic manipulation of CK metabolism is a potentially powerful tool to enhance seed yield [19,22]. Intriguingly, however, it was recently demonstrated that high levels of CKs in ckx7 mutants inhibited fruit elongation [23].…”
Section: Cytokinins Play a Pivotal Role In Ovule Patterning And Develmentioning
confidence: 98%
See 1 more Smart Citation